До питання про розвиток воєнного (військового) туризму в Україні - Щука Галина; Shchuka Halyna; Scsuka Halina; Несторишен Ігор; Nestoryshen Ihor; Медвідь Лариса; Medvid Larisa (Видавничий дім «Гельветика», 2024)
Резюме. Воєнний туризм є одним із перспективних напрямків розвитку туристичного бізнесу в Україні. В статті представлені сутність та структура даного виду туризму; виокремлено потенційні обмеження та основні виклики даного сегменту туристичного ринку. В результаті проведеного аналізу виявлено, що розвиток воєнного туризму гальмується відсутністю єдності у визначенні його сутності, ресурсних джерел та цільової аудиторії, що ускладнює нормативно-правове забезпечення даної діяльності, формування туристичного продукту та підготовку фахівців, які будуть працювати в даному секторі. Встановлено, які проблеми можуть бути вирішені на рівні держави, галузі, закладів вищої освіти, окремого регіону чи локації, туристичної фірми або ж вимагають їхньої співпраці.

Abstract. The relevance of the study is due to the prospects for the development of military tourism in Ukraine at the present time and after the end of active hostilities. The aim and objectives of the study are to analyze the essence and structure of this type of tourism, to identify the main challenges faced by this segment of the tourism market and the possibilities of their solution. The article applies systemic-structural and dialectical approaches to the consideration of the problems using the methods of analysis, synthesis, systematization, and modeling. It has been established that military tourism is a multi-segment phenomenon that unites all travels whose main motive is interest in military events and/or military equipment. These trips can be real and virtual, and can be made both to safe areas and to the zone of active hostilities. This type of tourism, like its subtypes, does not have a single name. The existing terminological uncertainty prevents the formation of a clear proposal. The controversial nature of the issue of whether travel to the area of active hostilities belongs to military tourism hinders the definition of the essence of this phenomenon and the development of regulatory support. This, in turn, does not allow to organize legal tourism activities in this segment and to guarantee travel safety; it affects the identification of tourist resources and territories that can be considered as tourist destinations. Obviously, this complicates the training of personnel for this segment of the tourism market and does not allow for the quality organization of work with local communities. A separate issue is the problem of interpreting the military heritage of the Soviet and imperial periods, since the entire territory of Ukraine was a zone of active hostilities of the First and Second World Wars, and this cannot be ignored when organizing military tours. It is found out that the existing problems should be solved at several levels: state (regulatory and legal support), sphere of tourism (development of standards, protocols, research on the needs of the target audience, ways to involve representatives of territorial communities and military retirees, etc.), higher education institutions (updating educational and professional programs), travel agencies (forming offers), by combining the efforts of state authorities, representatives of local self-government bodies, research and teaching staff, and business.
To the question of the development of war (military) tourism in Ukraine
Keywords: воєнний туризм; військовий туризм; поствоєнний туризм; туризм в період активних воєнний дій; воєнна спадщина